(3fbWI GdPgH aj eYQaI dSGf GdYQHs - (3GdYRj , Ydj Hf Ydj GdYRj, GdeNddGJj,J (B981 (3g` s ((3eMeO GdMfaj GdeNddGJj s)
(3ChdgG (B:s
(3eG gh GdcdGe? gh GddaX GdeQcH GdeajO HGdhVY GdYQHj s
(3BNQgG (B:s
(3fMh ecQ Gddjd Cj ecQ aj Gddjd hGdCUd efgG Cf Jchf Ydi eYfi GddGe hGddg CYde JeJ s
(3hVYg GdeDda Ydi Tcd SDGd hLhGH ddeHJOFjfs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B154s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B333 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdfMhs